Measuring Performance Using Balanced Scorecard: Case Study at SP Aluminium Yogyakarta - Noni Oktiana Setiowati; Siti Husna Ainu Syukri (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
Abstract Small and medium enterprises (SME) have become the backbone of Indonesia domestic economy and accountable for Indonesia Gross Domestic Product (GDP). Yogyakarta is known for many metal casting SMEs including SP Aluminium which produce household appliances and crafts. The competition between SMEs that continues to increase will require company performance measurements that are not only based on financial aspects, but also emphasize the balance of other aspects such as the Balanced Scorecard method. Currently, many SMEs such as SP Aluminium have never carried out performance measurements outside financial aspects, while non-financial aspects are also important for business development. The objective of this study is to measure SP Aluminium performance using Balanced Scorecard. The results showed that for the Financial Perspective, SP Aluminium had exceeded ROI and Profit Margin targets, but the Revenue Growth Indicator only reached the company target in 2013. For the Customer Perspective, Customer Profitability had exceeded the target and keeps increasing, but Customer Growth sharply decreased in 2015 and didn’t reach the company target. There are 3 indicators who meet the company target on Internal Business Process Perspective: Product Innovation, Operation Process, and After-sales Process. Meanwhile another indicator, Defective Product Ratio did not meet the company’s target. For Learning & Growth Perspective, Employee Productivity had exceeded the company target since 2013. Meanwhile for Employee Satisfaction indicator, 76,40% of the employees were satisfied working in SP Aluminium. But Work Accident indicator needs more attention because the measurements result showed that the accidents occurred in the company always increased every year and far exceeded the set target. Keyword: SME, Balanced Scorecard, Performance Measurement